Gambling in the Perspective of Criminal Law Policy - Toetik Rahayuningsih; Lailatul Mustaqimah (Universitas Airlangga, 2023)
AbstractGambling is an act that is prohibited in both the Criminal Code and social norms. However, the application of Article 303 and Article 303bis of the Criminal Code and Government Regulations related to controlling gambling only covers gambling crimes that occur within the territory of the Republic of Indonesia. The application of gambling as a crime can lose the nature of an unlawful act if the gambling gets permission from the authorities so that the gambling becomes legal or legal. In practice, there are still customs or cultures that think that gambling is part of the culture and is difficult to eradicate and even spreads to use technology. This study aims to evaluate the enforcement of gambling laws in the perspective of criminal law policy. This research is a doctrinal research using a conceptual approach and a legal approach. This study was conducted by looking at whether the development of law enforcement and the provisions stipulated in the Criminal Code can reach the crime of gambling and increase public awareness efforts related to gambling. The results show that it is necessary to establish an ideal enforcement model based on the principles of legal certainty, justice and avoid the emergence of a gambling perspective legalized in the name of culture.